Crecimiento, reproducción y dinámica poblacional de Anchoa mitchilli (Pisces: Engraulidae) en el sistema Palizada-Del Este, Campeche, México - Araya-Pérez, Luis Amado; Rojas- Galaviz, José Luis; Avilés-Alatriste, Obed Agustín (Revista de Biología Tropical, 1996)
A total of 640 Anchoa mitchilli were collected monthly in ten stations al Palizada-Del Este. Campeche, Mexico (August 1985 - July 1986). This the second species of the sile in abundancc and frequency of collection.is associalcd with estuarine aas muddy bottoms, salinily of 20.4 - 26.3 ppt and low water transparency (17.6-25.0%). Growth is allometric and the highest condition index is from August through March. It is a first order consumer with a diet rich in copepods and diatoms Population growth and monalily parameter are l.00=97 mm; K=O.614; Z=3.134; F=1.391; M=1.743; wilh a recruitment pulse in the yearly cycle: 294 were male, 310 females and 39 could not be sexed. Total length at first maturity was 45.8 at a male: female ratio of 1:1.4. It is suggested that Palizada-Del Este laguna de Térninos and the continental shelf are used for feeding maturation and reproduction, respectively